In light of the DSM-5 dimensional model of personality: Borderline personality disorder at the crossroads with the bipolar spectrum - Henriques-Calado, J.; Gonçalves, B.; Marques, C.; Moreira, A.; Paulino, M.; Marques, J.G.; Grácio, J.; Pires, R. (Journal of Affective Disorders, 2021)
Background. Research highlight that borderline personality disorder (PD) and bipolar spectrum disorders have clinical characteristics in common, which often imply uncertainty in differential diagnosis. Although there is a growing body of literature on the dsm-5 dimensional model of personality disorder, its discriminative features between these clinical samples are still understudied. In this study, we sought to identify the best set of predictors that differentiate between borderline PD and bipolar spectrum, based on pathological and normative personality traits and symptoms. Methods. A cross-sectional study of three clinical samples: 1) Borderline PD group of 63 participants; 2) Major depressive disorder group of 89 participants; 3) Bipolar disorder group of 65 participants. Self-reported assessment: Personality Inventory for DSM-5; Brief Symptom Inventory; FFM Inventory. A series of one-way ANOVAs and logistic regression analyses were computed. Results. The major set of data emerging as common discriminants of borderline PD across bipolar spectrum are unusual beliefs & experiences, paranoid ideation, obsession-compulsion and extraversion. Specifically, depressivity (OR: 34.95) and impulsivity (OR: 32.06) pathological traits displayed the greatest predictive values in the differential diagnostics. Limitations. The small size of the samples; no data from the previous clinical history and current treatment. Conclusions. Findings support the dsm-5 pathological traits as differentiating borderline PD through bipolar spectrum, and reinforce the joint use of symptom-related pathological functioning and normal-range personality traits. Alongside with bipolar spectrum, borderline pathology sheds light upon a hypothetical overlap along depressive and schizophrenia spectra, representing a borderland space in a crossroads with the psychopathology of meta-spectrum.